Контактная стыковая сварка трубопроводов - Кучук-Яценко С. И. Сергей Иванович; Кривенко В. Г. Валерий Георгиевич; Сахарнов В. А. Василий Алексеевич; Униговский М. Р. Михаил Робертович (Киев, Наук. думка, 1986)
Авт. указаны перед вып. дан.